Optimalisasi Kinerja Pegawai melalui Sinergi Kepemimpinan dan Budaya Organisasi: Studi pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas II Jayapura - Picanussa, Ghersom Alexander; Kambuaya, Balthasar; Syauta, Jack H. (Magister Manajemen Universitas Cenderawasih, 2024)
This study analyzes the influence of leadership and organizational culture on job satisfaction and employee performance at the Office of Harbormaster and Port Authority Class II Jayapura. Using the SEM-PLS method, this research finds that effective leadership and strong organizational culture positively and significantly affect job satisfaction, which in turn impacts the improvement of employee performance. The results indicate that leadership and organizational culture not only have a direct influence on performance but also indirectly through the mediation of job satisfaction. With a study population of 65 employees, a questionnaire instrument was used to measure the variables analyzed, namely leadership, organizational culture, job satisfaction, and employee performance. The findings emphasize the importance of an integrated approach between leadership and organizational culture to achieve optimal job satisfaction and performance. Recommendations are provided for organizations to develop leadership training programs and strengthen an innovative and supportive work culture. For future research, it is suggested to expand the population scope and consider other variables, such as work motivation, to enrich the study's findings. This research contributes to the development of a model for improving employee performance through the synergy of leadership and organizational culture.